2011
DOI: 10.1246/cl.2011.1283
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid-mediated ArSE Aroylation of Naphthalene Derivative: Distinct Second Aroylation Behavior of α-Naphthyl Ketone

Abstract: Dual ArSE aroylation of 2,7-dimethoxynaphthalene proceeds with distinct susceptibility and regioselectivity depending on the Lewis acid. The TiCl4-mediated reaction readily affords 1,8-diaroylated product. In the AlCl3-mediated reaction, monoaroylation essentially proceeds with partial ether cleavage and under some specific conditions 1,6-diaroylation proceeds in preference to 1,8-diaroylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 17 publications
0
48
0
Order By: Relevance
“…22 Synthetic methods and spectral data for the precursor, 1,8-bis(4-chlorobenzoyl)-2,7-dimethoxynaphthalene, have been reported in literature. 11,12,20 Measurements 1 H NMR spectra were recorded on a JEOL JNM-AL300 spectrometer (300 MHz). Chemical shifts are expressed in ppm relative to internal standard of Me4Si (δ 0.00).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Synthetic methods and spectral data for the precursor, 1,8-bis(4-chlorobenzoyl)-2,7-dimethoxynaphthalene, have been reported in literature. 11,12,20 Measurements 1 H NMR spectra were recorded on a JEOL JNM-AL300 spectrometer (300 MHz). Chemical shifts are expressed in ppm relative to internal standard of Me4Si (δ 0.00).…”
Section: Methodsmentioning
confidence: 99%
“…The authors' recent work has focused on peri-aroylnaphthalene compounds and the homologous/analogous substances. [11][12][13][14][15][16][17][18][19][20] According to the X-ray crystal structural analyses of ninety peri-aroylnaphthalene compounds, the two aroyl groups are non-coplanarly situated to the naphthalene ring and ordinary oriented in an opposite direction (anti-orientation). The molecular packing of peri-aroylnaphthalene compounds are mainly stabilized by cooperation of several kinds of weak non-covalent-bonding interactions, i.e., four kinds of nonclassical hydrogen bonds, (sp 2 )C-H···O=C hydrogen bond, (sp 3 )C-H···O=C hydrogen bond, (sp 3 )C-H···OR hydrogen bond, and C-H···π hydrogen-bonding interaction, and π···π stacking interaction are observed in decreasing order of frequency.…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, the naphthalene derivatives having aroyl groups at peri-positions, i.e., 1-aroyland 1,8-diaroylnaphthalene derivatives, are one of the good models for analysing non-covalent bonding interactions in crystal. Recently, the authors have found highly effective diaroylation at peri (1,8)-positions of 2,7-dialkoxynaphthalene [10,11]. Furthermore, functional group interconversion of 2-and/or 7-alkoxy group to hydroxyl group is also achievable [12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the aromatic ketone compounds bearing some restriction against structural alteration also have non-coplanar alignment of aromatic rings with relatively loose conformational fixation of substituents. Recently, the authors have found highly efficient diaroylation at peri (1,8)-positions of 2,7-dialkoxynaphthalene compounds [5,6]. peri-Aroylated naphthalene compounds thus obtained are proved to have non-coplanarly accumulated aromatic-rings-structure in crystal, i.e., the aroyl groups are twistedly situated to the naphthalene ring core in a perpendicular fashion [7][8][9].…”
Section: Introductionmentioning
confidence: 99%